Personalism in Latin American cultural area. - Bochatey, Alberto (Medicina e Morale, 2004)
The Author does a wide investigation on the development of bioethics in the cultural area of Latin America. The history of bioethics in this continent is strongly influenced from how much it happens in USA, namely the sharing of the principlist perspective (T.L. Beauchamp and J.F. Childress) applied to a series of specific fields, like clinical care, procreation and abortion, reproductive technologies, encephalic death (mainly in sight of the organ transplantation), research ethics, ecology. The ontologically founded personalistic bioethics is considered a very propitious field to intend, to orient toward the human person and its transcendent and social reality, to common good and the development in the medical field. Latin America is the continent of the hope and also the Latin American Bioethics (especially through the personalization of the "bios" and the claim of the communitarian and social dimension of the ethos). In such sense the personalist bioethics can contribute to the construction of a "bridge to the future" and to the Latin American integration and co-operation. Particular attention is dedicated to three meaningful themes: science and technology, Christian identity and role of the education, hospital ethics committees. For these and other fields, the reference to the personalism is a true challenge that involves an answer, an appointment and concrete actions.